2009
DOI: 10.1007/978-90-481-2672-9_6
|View full text |Cite
|
Sign up to set email alerts
|

Glacial to Holocene Paleoceanographic and Continental Paleoclimate Reconstructions Based on ODP Site 1233/GeoB 3313 Off Southern Chile

Abstract: ODP Site /GeoB 3313 located at the upper continental slope off southern Chile (41 • S) is ideally located to study latitudinal shifts of atmospheric and oceanographic circulation off southwestern South America. Extraordinarily high sedimentation-rates allow for high resolution reconstructions and detailed comparisons of various continental climate and paleoceanographic proxy records within the same archive avoiding problems linked to age model uncertainties. We discuss the major paleoclimatic findings of Site … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 90 publications
1
6
0
Order By: Relevance
“…When analysing cyclonic activity by the Eulerian method (kinetic energy), it is observed that positive anomalies in the Pacific and Atlantic indicate an increase in cyclonic activity (intensity), whose are more evident during the austral winter and spring for the El Niño period, while the negative anomalies of the kinetic energy, associated with the weakening of cyclonic activity, are observed during DJF and MAM for La Niña. According to Lamy and Kaiser (2009), during La Niña events the South Pacific Subtropical High becomes more intense and the STs are located south of 45°S, generating unfavourable conditions for precipitation to the north of this latitude, corroborating with our results, in particular in MAM. For the Indian Ocean, the results found are consistent with Reboita et al .…”
Section: Resultssupporting
confidence: 93%
“…When analysing cyclonic activity by the Eulerian method (kinetic energy), it is observed that positive anomalies in the Pacific and Atlantic indicate an increase in cyclonic activity (intensity), whose are more evident during the austral winter and spring for the El Niño period, while the negative anomalies of the kinetic energy, associated with the weakening of cyclonic activity, are observed during DJF and MAM for La Niña. According to Lamy and Kaiser (2009), during La Niña events the South Pacific Subtropical High becomes more intense and the STs are located south of 45°S, generating unfavourable conditions for precipitation to the north of this latitude, corroborating with our results, in particular in MAM. For the Indian Ocean, the results found are consistent with Reboita et al .…”
Section: Resultssupporting
confidence: 93%
“…Mix et al (2003) reported an 8-cm-thick dark ash layer of intermediate composition in the Ocean Drilling Program (ODP) site 1233, located 38 km offshore in more than 800 m water depth 260 km northwest from Michinmahuida Volcano. This layer has been dated between 10.5 and 11.0 ka BP (Lamy and Kaiser, 2009) and it has the highest magnetic susceptibility of the entire core at site 1233. However, glass chemistry for this tephra does not fit with Michinmahuida compositions (Table 2).…”
Section: Amarillo Ignimbritementioning
confidence: 99%
“…Drier conditions during the early to mid-Holocene have also been documented at Abarzúa et al, 2004;Moreno, 2004;Moreno and León, 2003). Sedimentary records from oceanic, fjord and lake sites from southern, central and northern Chile indicate widespread warming at southern hemisphere mid-latitudes between 490 12.5 and 8.5 cal ka BP (Lamy and Kaiser, 2009;Fletcher andMoreno, 2011, 2012;Kaiser et al, 2008;Kim et al, 2002;Lamy et al, 2010).…”
Section: Paleoclimate Implicationsmentioning
confidence: 90%